2014
DOI: 10.2139/ssrn.2443659
|View full text |Cite
|
Sign up to set email alerts
|

The Renminbi and Exchange Rate Regimes in East Asia

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
2
4

Year Published

2015
2015
2019
2019

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 12 publications
0
4
2
4
Order By: Relevance
“…The table clearly indicates that the US dollar is still assigned the largest and predominant weight throughout the sample period, while other major international currencies such as the euro and the yen only have limited, occasional influence on the RMB exchange rate. Source: Kawai and Pontines (2015).…”
Section: Frankel-wei Estimation Of a Currency Basketmentioning
confidence: 99%
“…The table clearly indicates that the US dollar is still assigned the largest and predominant weight throughout the sample period, while other major international currencies such as the euro and the yen only have limited, occasional influence on the RMB exchange rate. Source: Kawai and Pontines (2015).…”
Section: Frankel-wei Estimation Of a Currency Basketmentioning
confidence: 99%
“…Nevertheless, Kawai and Pontines (2014a) observed that some of the Asian currencies (Korean won, Taiwan dollar and Singapore dollar) were also affected by the CNY movements from July 2010 to July 2013, despite their dependence on USD. Kawai and Pontines (2014b) in their subsequent research suggested that it is possible for the CNY to become an anchor currency in East Asia someday, driven by an increasingly important role of CNY in the regional currency baskets. 3 Shu et al (2014) agreed that the larger influence of CNY on Asia-Pacific is likely, due to recent reforms in the China's exchange rate policy.…”
Section: Introductionmentioning
confidence: 99%
“…Its 2.79 per cent share of global payments is dwarfed by the 45 per cent share of the dollar. 20 The dollar is still the preferred reserve currency (Kawai and Pontines 2014). The dollar is still far and away the dominant currency in global foreign exchange markets, where it is involved fully in 85 per cent of all transactions, according to the Bank for International Settlements' most recent triennial survey.…”
Section: The Case For a Regional Currencymentioning
confidence: 99%